Legal Considerations in Appointing a Marriage Guardian for a Child Born Out of Wedlock - Limonu, Hardiyanto Putra (Universitas Negeri Gorontalo, 2024)
Marriage, as a sacred bond encompassing both physical and spiritual dimensions, necessitates recognition under positive law. This study aims to identify and analyze the legal status of marriage guardians for children born out of wedlock and the factors influencing the determination of such guardianship in Gorontalo City. Utilizing an empirical research approach, the study examines relevant legal frameworks and administrative practices. The analysis reveals that in Gorontalo City, the legal status of marriage guardians for children born out of wedlock is generally assigned to a court-appointed guardian. However, if the child is born more than six months after the parents' marriage, a lineage-based guardian may be appointed instead. Additionally, nine Religious Affairs Offices consistently apply the same legal status for children born out of wedlock. The factors influencing the determination of marriage guardianship in Gorontalo City include the completeness of the prospective bride and groom's documentation. The findings highlight the importance of standardized legal procedures to ensure the protection and welfare of children born outside of marriage.